Testing method for objective evaluation of cross-country ski poles - Swaren, M.; Therell, M.; Eriksson, A.; Holmberg, H. C. (Sports Engineering, 2013)
The aim of the study was to develop an objective classification method for cross-country ski poles. A test device was designed to expose different pole models to maximal loading and impact tests. A load cell measured the axial forces in the pole shafts, and a laser distance meter measured shaft deflection when a load was applied via the wrist strap. In the loading tests, each shaft reached a plateau where no more force could be transferred. This maximal force transfer (MFT) value was a characteristic measure for flexural rigidity and thereby also strength. The developed test method enables a loading that is more similar to real-life skiing than a standard three-point bending test. Results show that the introduction of shaft indices for buckling strength is beneficial for comparison purposes. The MFT is a relevant parameter used in the characterization of poles.